2008
DOI: 10.1186/1471-2180-8-97
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Aspergillus fumigatus conidia by primary nasal epithelial cells in vitro

Abstract: Background: Invasive aspergillosis, which is mainly caused by the fungus Aspergillus fumigatus, is an increasing problem in immunocompromised patients. Infection occurs by inhalation of airborne conidia, which are first encountered by airway epithelial cells. Internalization of these conidia into the epithelial cells could serve as a portal of entry for this pathogenic fungus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 27 publications
4
64
0
1
Order By: Relevance
“…The internalized conidia were quantified using the fluorescence brightener Blankophor-P-fluessig [4,49-bis[(4-anilino-6-substituted-1,3,5-trazine-2-yl) amino stilbene-2,29-disulfonic acid], kindly provided by Bayer (Botterel et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The internalized conidia were quantified using the fluorescence brightener Blankophor-P-fluessig [4,49-bis[(4-anilino-6-substituted-1,3,5-trazine-2-yl) amino stilbene-2,29-disulfonic acid], kindly provided by Bayer (Botterel et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…We used in our study Penicillium chrysogenum as a control for conidia ingestion (Botterel et al, 2008). P. chrysogenum is a mould that is highly predominant in the environment, with a conidial size (3-4 mm diameter) similar to that of A. fumigatus.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, an in vitro study has shown that PAR 2 activation on monocytes enhanced the suppressive effects of IFN-␥ on IAV replication (21). The role of PAR 2 activation in other cell types and particularly in epithelial cells, one of the primary cell types exposed to different pathogens and to IAV (22,23), has never been studied in the context of viral infection. Furthermore, the specific role of PAR 2 activation in in vivo in models of viral infection has never been addressed.…”
Section: Nfluenza Virus Type a (Iav)mentioning
confidence: 99%
“…3). Similarly, human nasal ciliated epithelial cells phagocytose and kill conidia in vitro (20). A human alveolar epithelial cell line (A549) can bind both Aspergillus conidia and hyphae, ingest conidia, and generate IL-6 and CXCL8 in response to them (75,177).…”
Section: Epithelial Cellsmentioning
confidence: 99%